Structural Stability of Ni/Al Layered Double Hydroxide Supported on Graphite and Biochar Toward Adsorption of Congo Red - Patimah Mega Syah Bahar Nur Siregar; Neza Rahayu Palapa; Alfan Wijaya; Erni Salasia Fitri; Aldes Lesbani (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2021)
In this research, Ni/Al layered double hydroxide (LDH) was modified by using co-precipitation method to generate Ni/Al-graphite (Ni/Al-GF) and Ni/Al-biochar (Ni/Al-BC). The adsorbents were applied to remove Congo Red from aqueous solution. The obtained samples were characterized by using XRD, FTIR, BET and TG-DTA. The XRD diffraction pattern of Ni/Al LDH, Ni/Al-GF, and Ni/Al-BC presented the formation of composite with decreasing crystallinity. The surface area modified LDHs was higher than the pristine materials, which was obtained 15.106 m2/g, 21.595 m2/g and 438.942 m2/g for Ni/Al-LDH, Ni/Al-GF, Ni/Al-BC respectively. The adsorption of Congo Red on the materials was tested at dierent parameters and the results exhibited that Congo Red adsorption on LDHs were pseudo-first-order (PFO) kinetic, spontaneous, endothermic and followed Langmuir model. The adsorbents removed Congo Red by high performance stability with adsorption capacity was 116.297 mg/g for Ni/Al-GF and 312.500 mg/g for Ni/Al-BC. These adsorption capacity was higher than the pristine LDH (61.728 mg/g). The regeneration process which carried out for five cycles showed that Ni/Al-GF and Ni/Al-BC have stable structures as reuse adsorbents for Congo Red from aqueous solution.